Pneumatic Insufflation to Confirm Distal Stoma When in Doubt - Akshay Kumar Saxena; Pavithra Subramanian; Anmol Bhatia; Kushaljit Singh Sodhi (Indian Journal of Radiology and Imaging, 2024)
Background Distal colostogram and ileostogram are commonly performed radiological procedures in the pediatric population. It is sometimes difficult to identify the distal stoma while performing these procedures.